Ecological Impacts of Altered Stream Hydrogeomorphic Characteristics Extend Beyond the Channel Boundary: Evidence From Urban Streams of Columbus, OH, United States - Rieck, Leslie O.; Sulliván, S. Mažeika Patricio (Frontiers in Ecology and Evolution, 2022)
Urbanization in stream catchments can have strong effects on stream channel hydrogeomorphic features including channel dimensions, channel-floodplain connectivity, and flood regime. However, the consequences of hydrogeomorphic alterations on aquatic-terrestrial subsidy dynamics remain poorly resolved. We examined the associations among hydrogeomorphic characteristics, emergent aquatic insect assemblages, and the density and trophic dynamics of riparian spiders of the family Tetragnathidae at 23 small urban stream reaches in the Columbus, Ohio (USA) Metropolitan Area. Naturally abundant stable isotopes of 13C and 15N were used to quantify the relative contribution of aquatically-derived energy (i.e., nutritional pathways deriving from algae) to tetragnathid spiders and their trophic position. Bankfull discharge was negatively related to both emergence rate and family richness. On average, tetragnathid spiders relied on aquatically-derived energy for 36% of their nutrition, with the greatest reliance found for spiders next to channels with wider flood-prone widths and proportionally fewer emergent insects of the family Chironomidae. Mean emergent aquatic insect reliance on aquatically-derived energy was 32% and explained 44% of the variation in tetragnathid aquatically-derived energy. A positive relationship between δ13C of tetragnathid spiders and emergent insects provides additional evidence of tetragnathid reliance on emergent insects. Mean tetragnathid trophic position was 2.85 and was positively associated with channel sinuosity and negatively associated with aquatic insect emergence rate. Sinuosity was also positively related to aquatically-derived energy of emergent aquatic insects, as well as emergent insect family richness, %EPT, and aquatic insect emergence rate, implicating instream habitat-mediated shifts in emergent aquatic insect communities as an indirect mechanistic link between hydrogeomorphic processes and spiders. Our findings underscore that the impacts of stream hydrogeomorphic alterations can cascade into terrestrial food webs. These results suggest that monitoring and restoration of fluvial geomorphic form and function (e.g., sinuosity, slope, hydrology) confer benefits to both aquatic and terrestrial riparian ecosystems in urban catchments.